Representações de infância, brinquedo, brincar e consumo na animação Toy Story (1995) - Dal Prá, Rayany Mayara (2017)
This research analyzes childhood representations, toy, play and consumption in Toy Story (1995) American animation, produced by the partnership between Walt Disney Pictures Studios and Pixar Animation Studios, directed by John Lasseter and screenplay by Michel Arndt. This film has become a milestone in film history because it was the first one totally produced with computers. In the animation, toys come to life when their owners, the children, are not present. In this sense, problematizing what these toys are and who plays with them is one object of this research. In addition, we also reflect on how playing is represented. Considering the film as a product of the Cultural Industry, we make some reflections on the consumption in the animation as another object of analysis. The study indicates that in Toy Story (1995), the childhood is represented as a universe apart compared to adult world and that the toys are, for excellence, the cultural artifacts that indicate the children's belonging to this social category. However, it does not refer to any toy or any child. There is a distinction between the toys of the "ideal child" and the child that needs to be "educated". There is also a differentiation between toys for girls and those belonging to the boys, indicating stereotypes of masculinity and femininity. The way children relate to these toys also indicate "correct" and "incorrect" ways of playing. As a web that links all these elements of the work, there is in the film itself, a consumer network that transposes cinema screens and invades the shelves of various commercial segments designated to children, which were analyzed based on the concept of transmedia. We conclude by pointing out the need for a pedagogy that considers the media and its culture as elements of learning and reading.